Unusual presentation of idiopathic sweet′s syndrome in a photodistributed pattern - Rajesh Verma; Biju Vasudevan; Vijendran Pragasam; Debdeep Mitra (Indian Journal of Dermatology, 2014)
A 40-year-old lady presented with history of multiple red raised painful lesions over her body of 10 days duration. Lesions spread from forearms to arms and back of trunk during the progress of the disease. Associated pain and burning sensation in the lesions was present while working in the sun. Mild to moderate grade fever, malaise, pain over large joints, decreased appetite, and redness of eyes was also present. There was no history of drug intake or other risk-factors. Dermatological examination revealed erythematous papules coalescing to form plaques with a pseudovesicular appearance over the extensor aspect of forearms and photo-exposed areas on the back of trunk. There was a sharp cut-off between the lesions and the photo-protected areas. Investigations revealed anemia, neutrophilic leukocytosis, raised erythrocyte sedimentation rate and positive C reactive protein. Skin biopsy showed characteristic features of Sweet′s syndrome. No evidence for any secondary etiology was found. She responded to a tapering course of oral steroids and topical broad spectrum photo-protection. This case is a very rare instance of idiopathic Sweets syndrome occurring in a photo-distributed pattern.